Modernisasi Pendidikan Islam; Telaah Pemikiran Muhammad Abduh - Abdul Malik Usman; Mardan Umar (Jurnal Ilmiah Iqra', 2021)
Modernization of Islamic Education; A Study of Muhammad Abduh's Thoughts. This paper tries to present the great ideas of Sheikh Muhammad Abduh, (Muhammad bin Abduh bin Hasan Khairullah), who is widely known as a progressive thinker, movement activist, and also an Egyptian-born mujaddid, the founder of the reform movement and modernization of Islamic education, towards modern Egypt. This study is a literature study using a qualitative approach and content analysis techniques on Muhammad Abduh's thoughts. The results of this study indicate that there is a dialectic process between Muhammad Abduh's great ideas and the Egyptian social situation, both internally by Muslims with traditional Islamic views - conventional and external situations of the European nation and its modern civilization which is currently colonizing Egypt. The idea of reforming and modernizing Islamic education includes: the conventional teaching system is only religious sciences, equipped with modern general knowledge, accompanied by curriculum improvements that combine tanziliyyah sciences with Kauniyyah sciences, (Islam and modernity), eradicating dualism and dichotomy views of science. , improvement of learning systems and methods that emphasize understanding and reasoning, as well as women's education. As a result, Egypt has become a cauldron of moderate Islamic education leaders until now